แนวทางการจัดการและพัฒนาบุคลากรสายสนับสนุนการศึกษาในโรงเรียนมัธยมศึกษา สังกัดสำนักงานคณะกรรมการการศึกษาขั้นพื้นฐาน - พงศ์นที คงถาวร (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
The purposes of this study were 1) to study the current state and expectations for management and development of support staff in secondary schools and 2) to propose guidelines for management and development of support staff in secondary schools under the Office of Basic Education Commission (OBEC). The population was 239 extra-large secondary schools under OBEC. The sample of 80 extra-large secondary schools was purposively selected from 40 Secondary Educational Service Area Offices (SESAO) possessing extra-large secondary schools. In fact, there were all together 42 Secondary Educational Service Area Offices under OBEC but 40 areas had extra-large secondary schools. Two schools were selected from each SESAO. The informants consisted of 400 officials serving the positions as school directors and deputy directors from the 4 main school functions (academic, general administrative, budgetary, and personnel administrative). The current state and expectations were examined using a 5-point Likert scale questionnaire. Data analysis included means and standard deviations calculation as well as the Modified Priority Needs Index Method (PNImodified). The guidelines for management and development of support staff were explored using interview and content analysis methods. The participants for interviewing were 5 schools. The school directors and deputy directors from the 4 main school functions, mentioned earlier, were selected, making in total 25 participants for interviewing. Concerning the management of support staff in the current state, it reviewed that performance appraisal was the highest average. Regarding the expectations, job analysis and design and performance appraisal were both appeared to be the highest averages. The PNImodified results suggested that compensation and benefits were most needed. As regards the development of support staff, both the current state and expectations had in-school supervision planning as highest averages. The PNImodified results suggested that under in-school supervision, the following aspect were most needed for a study: the current state, problems, and needs. The guidelines for the management of support staff consisted of six aspects: job analysis and design, staff planning, recruitment and selection, performance appraisal, compensation and benefits, and career path. The guidelines for support staff development through in-school supervision processes comprised of five aspects: a study on the current state, problems and needs, planning, instrumentation, operation of in-school supervision, and evaluation of activities.